Representation of black, young, women politicians in South African online news media : a case study of Lindiwe Mazibuko - Mannya, Maphuti Mabothakga (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.